Pengembangan Bahan Ajar Smp Kelas Vii Dengan Tema Peristiwa Alam Melalui Kajian Teks Eksplanasi Dalam Buku Bencana Alam Dan Bencana Anthropogene Karya Sukandarrumidi - Sa-ah, Miss Suhainee, Drs. Agus Budi Wahyudi,M.Hum (2016)
This study aims to: (1) determine the explanatory text in the book Natural Disasters and Disaster Anthropogene by Sukandarrumidi. (2) describe the substance of the book Disasters Alama and Disaster Anthropogene, making it feasible to be used as material development in junior high school in grade VII with the theme Nature events through the study of explanationtexts. Researcher took this title because it wanted to develop the text material of explanation in the handbook of junior high school students of class VII at first semester. This qualitative descriptive research using the data in the form of explanatory text in the book Natural disasters and Disaster Anthropogene by Sukandarrumidi. The technique of collecting data in this research is equivalent method. The validity of data in this research is using triangulation technique of data source. The results of this study: (1) theexplanationtextin the book Natural Disasters and Disaster Anthropogene by Sukandarrumidi has appropriated with structure of explanation text (general statement, row explanation, interpretation) and in accordance with KD 3.1 and 4.1, (2) The text in the book Natural disasters and Disaster Anthropogene by Sukandarrumidi already eligible to serve as the development of teaching materials in junior high school in grade VII first semester because it provides useful information for students, such as the "Earthquake", "Fire", "Tsunami Hazard", and etc. Keyword: Explanation text, Natural Disasters and Disaster Anthropogene book, Development teaching material